A Data Driven Approach to Investigate the Chemical Variability of Clinopyroxenes From the 2014–2015 Holuhraun–Bárdarbunga Eruption (Iceland) - Caricchi, Luca; Petrelli, Maurizio; Bali, Eniko; Sheldrake, Tom; Pioli, Laura; Simpson, Guy (Frontiers in Earth Science, 2020)
The Holuhraun-Bárdarbunga eruption lasted approximately 6 months. Magma propagated laterally through a 40 km long dyke, while Bardarbunga caldera was collapsing. This event was intensely monitored, providing an opportunity to investigate the relationships between eruption dynamics and erupted products. Whole rock and melt inclusion data do not show chemical variations of magma during the eruption. Nevertheless, zoning patterns in clinopyroxene suggest temporal variations of intensive parameters during crystallisation. We investigated the chemical zoning of clinopyroxene using a data driven approach, on major and trace elements analyses from lava flow lobes emplaced during the eruption. We applied hierarchical clustering to identify compositional groups based on major and trace element chemistry. This analysis identifies 5 compositional groups, which can be associated with specific petrographic features. One cluster represents the chemistry of hourglass sectors, two constitute the oscillatory zoned mantle of the crystals, one cluster corresponds to a seldom present bright rim (in back scattered electron images) in the outer portions of the crystals, and a last one represents most of the outer rims. HC applied to trace elements also identifies 5 compositional clusters, which highlight progressively more evolved clinopyroxene compositions from the core to the rim of the crystals. Two of the clusters identified with trace elements corresponds to major element clusters. All together the data suggest that the chemical zoning in the inner portions of the clinopyroxene crystals was generated by crystallisation in the magma reservoir and interaction between hot magma propagating through the dyke and unerupted magma cooling within the dyke. The fraction of zones produced by interaction with colder portion of the magma residing within the dyke dropped during the eruption, potentially signalling the thermal maturation of the dyke. Some of the analyses reveal that relatively close to the eruption time (i.e the outer portions of the crystals) the dyke intercepted a lens of low temperature magma with a chemical composition that is distinguishable from the 2014-2015 Bardarbunga eruption. Our approach can provide insights on the evolution of deep processes occurring during long-lasting eruptions by combining the analysis mineral chemistry of erupted products with multiparametric monitoring signals.